Executive functioning in children with unilateral cerebral palsy: Protocol for a cross-sectional study - Bodimeade, H.; Whittingham, K.; Lloyd, O.; Boyd, Roslyn (2013)
Introduction: Early brain injury, as found in children with unilateral cerebral palsy (CP), may cause deficits in higher-order cognitive tasks known as executive functions (EF). EF has been conceptualised as comprised of four distinct yet inter-related components: (1) attentional control, (2) cognitive flexibility, (3) goal setting and (4) information processing. The aim of this study was to examine EF in children with unilateral CP and compare their performance with a typically developing reference group (TDC). The potential laterality effects of unilateral CP on EF will be explored, as will the relationship between the cognitive measures of EF, behavioural manifestations of EF, psychological functioning and clinical features of unilateral CP. Methods and analysis: This cross-sectional study aims to recruit a total of 42 children with unilateral CP (21 right unilateral CP and 21 left unilateral CP) and 21 TDC aged between 8 and 16 years. Clinical severity will be described for gross motor function and manual ability. Outcomes for cognitive EF measureswill include subtests from the Wechsler Intelligence Scale for Children-Fourth Edition, Delis-Kaplan Executive Function System, Rey Complex Figure Test and the Test of Everyday Attention for Children. Behavioural manifestations of EF will be assessed using the Behaviour Rating Inventory of Executive Function, Parent and Teacher versions. Psychological functioning will be examined using the Strengths and Difficulties Questionnaire. Between-groups differences will be examined in a series of one-way analyses of covariance and followed up using linear comparisons. An overall composite of cognitive EF measures will be created. Bivariate correlations between the EF composite and psychological measures will be calculated. Ethics and dissemination: This protocol describes a study that, to our knowledge, is the first to examine multiple components of EF using a cohort of children with unilateral CP. Exploration of potential laterality effects of EF among children with a congenital, unilateral brain injury is also novel. Possible relationships between EF and psychological functioning will also be investigated. Ethics have been obtained through the University of Queensland School of Psychology Ethics Committee and the Queensland Children's Health Services Human Research Ethics Committee. Results will be disseminated in peer reviewed publications and presentations at national and international conferences. This study is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12611000263998).